Institutional challenges and stakeholder perception towards planned water reuse in peri-urban agriculture of the Bengal delta. (1st April 2021) - Haldar, Kamonashish; Kujawa-Roeleveld, Katarzyna; Schoenmakers, Marco; Datta, Dilip Kumar; Rijnaarts, Huub; Vos, Jeroen
Abstract: The indirect, unplanned use of urban wastewater by peri-urban farmers in developing countries poses a severe risk to the environment and the farmers. Planned water reuse could contribute substantially to the irrigation water demand in peri-urban agriculture and minimize the risk. However, implementing such practice requires a thorough evaluation of stakeholder's perception and the scope within the existing organizational structures. This paper aims to assess the level of awareness, perception, and willingness of different stakeholders toward current practices and the prospect of urban water reuse in Khulna City - one of the most vulnerable cities located in the southwest of Bangladesh due to the consequences of rapid climate changes in the Bengal delta. Also, institutional arrangements and their functioning were analyzed to understand the current sectoral performance. One questionnaire with 385 respondents from the urban area, 32 in-depth interviews and one focus group discussion with farmers in the peri-urban area, and ten interviews with key informants from the government and non-government organization was conducted. Results indicate an overall positive attitude among major stakeholder groups toward planned water reuse for peri-urban agriculture. More than half of the citizens (53%) are willing to pay for the treatment of wastewater and majority of the farmers (66%) are willing to pay for the supply of better-quality irrigation water. However, the public sector responsible for wastewater collection and treatment requires adjustment in rules and regulations to implement planned water reuse. Interrelated factors such as lack of transparency and coordination, shifting responsibilities to other organizations, lack of required resources need to be addressed in the updated rules and regulations. Strategies to enforce current regulations and align all stakeholders are also crucial for collection and treatment of wastewater and its subsequent use for crop production. Graphical abstract: Image 1 Highlights: Major stakeholder groups have positive attitude for urban water reuse. Education is the most significant factors for perception towards reuse. Polarization of water governance is hindering the direct measure for planed reuse. Authorities should not only rely on water tariffs for operation and maintenance.